Management : Challenges for tomorrow's leaders - Goodman, Stephen H.; Fandt, Patricia M.; Lewis, Pamela S.; Michlitsch, Joseph F. (South-Western, 2007)
This book includes a number of features designed to prepare students to be leaders in this new millennium: (1) meeting the challenges inherent in a dynamic, rapidly changing business environment, (2) developing the competencies and skills that leaders will need in the future, (3) bridging the gap between management theory and practice, and (4) responding to the contemporary management trends that will affect both organizations and managers in the 21st century.